The very peculiar cow: and other stories - Blyton, Enid; Silcock, Sara (Award Publications London, 2005)
The Very Peculiar Cow: And Other Stories by Enid Blyton is a collection of enchanting short stories filled with whimsical characters and humorous situations. The title story revolves around a peculiar cow who behaves in unusual ways, bringing delight and surprise to those around her. The collection also includes tales about magical happenings, mischievous animals, and imaginative adventures. Each story is crafted with Blyton's characteristic charm, offering young readers lessons in kindness, curiosity, and the wonders of everyday life. The lighthearted tone and creative storytelling make it an engaging read for children.